Prozhektor perestroiki . Prozhektor perestroiki . The Perestroika Spotlight . Прожектор перестройки - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. The program raises issues of corruption and includes a discussion on the role of the program "The Perestroika Spotlight" in resolving factories' raw material usage problems. Contributors: Chekalin, Stanislav (Anchor) Series description: Informational and analytical program, broadcasted in the Soviet Union in the late 1980's. The program was made during the “glasnost” period and was intended to describe and criticize the set of reforms. Коррупция. Роль передачи "Прожектор Перестройки" в разрешении проблем утилизации сырья на предприятиях. Создатели: Чекалин, Станислав (Ведущий/Ведущая) Описание серии: Информационно-аналитическая телепередача в СССР конца 80-х годов. Передача была создана в период гласности для освещения и критики проводимых в стране реформ.